Multi-Factor Of Employee Values: A Confirmatory Factor Analytics (CFA) Validation - M. R., Abdul Hamid; Zainol, Mustafa; N. R. M., Suradi; Fazli, Idris; M., Abdullah (Academic Journals, 2011)
Employees are an asset to the organisation and therefore, values that surround them have to be empowered for the benefit of the organisation. This article examines the factor structure of employee values which are fairness, consultative, mutual trust, acknowledgement, altruism and empowerment. Questionnaires were distributed to staff at the selected Higher Education Institution (HEI) in the east coast of Malaysia. The data collected was analysed using confirmatory factor analytic (CFA) approach in order to test the 6-factor hypothesized model of employee values. The revised hypothesized CFA model yielded a p-value of 0.180, normed chi-square of 1.329, CFI of 0.995, TLI of 0.990, GFI of 0.960 and RMSEA of 0.054 that suggested 4 core values, that is, fairness, consultative, mutual trust and altruism that dominantly explained the university’s employee values in the selected university. Besides,Bayesian estimation was then employed to cross-validate and support the modeling result obtained from the maximum likelihood (ML) estimation. Both Bayesian and ML estimation results are comparatively agreed to each other. The findings may pave the way forward for empowering values adoption and embracement for employees especially at the HEI in Malaysia.